2013
DOI: 10.1175/mwr-d-12-00352.1
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Software System Dependency of a Global Atmospheric Model

Abstract: This study presents the dependency of the simulation results from a global atmospheric numerical model on machines with different hardware and software systems. The global model program (GMP) of the Global/Regional Integrated Model system (GRIMs) is tested on 10 different computer systems having different central processing unit (CPU) architectures or compilers. There exist differences in the results for different compilers, parallel libraries, and optimization levels, primarily a result of the treatment of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In summer (Fig. 2), there is a very large spread of model responses with some RCMs predicting a widespread cooling from forestation (CCLM-TERRA and RCA), a widespread warming (RegCM-CLM4.5, REMO-iMOVE and the WRF Davies (1976) Davies (1976) Davies (1976) Davies (1976) Turbulence and planetary boundary layer scheme Level 2.5 closure for turbulent kinetic energy as prognostic variable (Mellor and Yamada, 1982) Level 2.5 closure for turbulent kinetic energy as prognostic variable (Mellor and Yamada, 1982) Level 2.5 closure for turbulent kinetic energy as prognostic variable (Mellor and Yamada, 1982) (Vogelezang and Holtslag, 1996) (Iacono et al, 2008) RRTMG scheme (Iacono et al, 2008) RRTMG scheme (Iacono et al, 2008) Tiedtke (1996) for cumulus convec-tion (Tiedtke, 1989) with modifications after Nordeng (1994) Grell and Freitas (2014) for cumulus convection and Global/Regional Integrated Model system (GRIMs) Scheme (Hong et al, 2013) for shallow convection (Kain, 2004); no shallow convection (Kain, 2004); no shallow convection Microphysics scheme one-moment cloud micro-physics scheme (Seifert and Beheng, 2001) one-moment cloud microphysics scheme (Seifert and Beheng, 2001) one-moment cloud microphysics scheme (Seifert and Beheng, 2001) values from tables models) or a mixed response (CCLM-VEG3D and CCLM-CLM4.5). Overall this highlights the strong seasonal contrasts in the temperature effect of forestation and the larger uncertainties associated with the summer response.…”
Section: Temperature Responsementioning
confidence: 99%
“…In summer (Fig. 2), there is a very large spread of model responses with some RCMs predicting a widespread cooling from forestation (CCLM-TERRA and RCA), a widespread warming (RegCM-CLM4.5, REMO-iMOVE and the WRF Davies (1976) Davies (1976) Davies (1976) Davies (1976) Turbulence and planetary boundary layer scheme Level 2.5 closure for turbulent kinetic energy as prognostic variable (Mellor and Yamada, 1982) Level 2.5 closure for turbulent kinetic energy as prognostic variable (Mellor and Yamada, 1982) Level 2.5 closure for turbulent kinetic energy as prognostic variable (Mellor and Yamada, 1982) (Vogelezang and Holtslag, 1996) (Iacono et al, 2008) RRTMG scheme (Iacono et al, 2008) RRTMG scheme (Iacono et al, 2008) Tiedtke (1996) for cumulus convec-tion (Tiedtke, 1989) with modifications after Nordeng (1994) Grell and Freitas (2014) for cumulus convection and Global/Regional Integrated Model system (GRIMs) Scheme (Hong et al, 2013) for shallow convection (Kain, 2004); no shallow convection (Kain, 2004); no shallow convection Microphysics scheme one-moment cloud micro-physics scheme (Seifert and Beheng, 2001) one-moment cloud microphysics scheme (Seifert and Beheng, 2001) one-moment cloud microphysics scheme (Seifert and Beheng, 2001) values from tables models) or a mixed response (CCLM-VEG3D and CCLM-CLM4.5). Overall this highlights the strong seasonal contrasts in the temperature effect of forestation and the larger uncertainties associated with the summer response.…”
Section: Temperature Responsementioning
confidence: 99%
“…By chance, we found that even tiny numerical precision errors due to the use of different computational architecture can lead to large differences in TC development, which is also found in Hong et al . []. Using exactly the same initial conditions and model setups, the SH5 ensemble set was run on two supercomputers at the Texas Advanced Computing Center (TACC): Ranger (Figure a), which has since been retired and replaced by Stampede (Figure b).…”
Section: Intrinsic Versus Practical Limits Of Predictabilitymentioning
confidence: 99%
“…They all came to the same conclusion that changes in behavior induced by hardware or software differences were not negligible compared to other sources of error such as uncertainty in model parameters or initial conditions. These conclusions were found to hold from weather (Thomas et al, 2002) to seasonal (Hong et al, 2013) and even climate change (Knight et al, 2007) time scales.…”
Section: Origins Of Non-replicabilitymentioning
confidence: 76%